2022
DOI: 10.3390/medicina58060704
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Wave Velocity, a Predictor of Major Adverse Cardiovascular Events, and Its Correlation with the General Stress Level of Health Care Workers during the COVID-19 Pandemic

Abstract: Background and Objectives: In the COVID-19 epidemiological context, the health care workers who were treating patients with COVID-19 were exposed daily to additional stress. Pulse wave velocity (PWV) is a predictive parameter for possible major adverse cardiovascular events. The present study aimed to evaluate the correlation between the general stress levels and PWVs of medical workers during the COVID-19 pandemic. Materials and Methods: The study group was heterogeneous in terms of the medical profession. PW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…Empirical studies have provided insights into the connection between occupational stress, burnout, and pulse wave velocity. For example, a study by Kamarck et al [46,47] found that higher levels of chronic work-related stress were associated with increased PWV. Similarly, Tsai et al [48] demonstrated that burnout was independently associated with higher PWV, suggesting a potential link between psychological well-being and cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies have provided insights into the connection between occupational stress, burnout, and pulse wave velocity. For example, a study by Kamarck et al [46,47] found that higher levels of chronic work-related stress were associated with increased PWV. Similarly, Tsai et al [48] demonstrated that burnout was independently associated with higher PWV, suggesting a potential link between psychological well-being and cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the work of Kume et al [15], even after only 5 min of mental stress, significant elevations of segmental PWV were recorded, and the changes persisted until 30 min in the group that simply rested on a chair after the mental stress test. A recent study [16] analyzed the association between PWV and general stress in a group consisting of medical staff. In this study, it was reported that working in a hospital during COVID-19 pandemic conditions led to increased PWV values compared to those measured in nonpandemic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…where E is the artery elastic (tangent) modulus, h is the artery wall thickness, r is the arterial radius, and ρ is the blood density. Due to the direct relation between PWV and E, PWV is the most commonly measured index of arterial stiffness and is a robust marker for future cardiovascular events (Kim et al 2020, Sequí-Domínguez et al 2020, Kim et al 2022, Marin et al 2022. In medical practice, some serious pathological deviations associated with the state of the vascular walls are diagnosed using measured PWV values, and the dynamics of their development is monitored (Crim et al 2020, Demir et al 2020, Mueller et al 2020, Filip et al 2021, Anastasio et al 2022, Helleputte et al 2022.…”
Section: Introductionmentioning
confidence: 99%